Hernia GWAS summary statistics - Wiberg, A; Ahmed, W; Furniss, D (University of Oxford, 2022)
Summary statistics for GWAS of four different abdominal hernia subtypes (inguinal, femoral, umbilical, hiatus), and two mixed hernia cohorts ("overlap hernia" and "umbrella hernia"). See our related publication for cohort definitions and case/control numbers: Ahmed W and Patel M, et al., PLOS ONE, 2022. SNP = SNP name; CHR = chromosome number; BP = genomic position (GRCh37); ALLELE1 = effect allele; ALLELE0 = non-effect allele; A1FREQ = frequency of effect allele; INFO = INFO score for imputed SNPs; BETA = beta coefficient; SE = standard error; PVAL = p-value.